The Legal Protection against the Criminalization of Notary Positions and Land Deed Officials (PPAT) - Irfan, Irfan; Arifullah, Achmad (Jurnal Konstatering, 2023)
It cannot be hidden, the position of the perpetrators of the position of notary public and land deed official (PPAT) is very vulnerable to becoming a â€œtarget for shootingâ€ by law enforcement officials. The term that is currently viral is "Criminalization" by unscrupulous officials with various motives. Meanwhile, in work, notaries are always reminded to be professional and comply with the applicable laws and regulations that regulate standard work procedures. This is regulated, mainly in the Notary Office Law, and other regulations, including the Regulations for the position of a land deed official (PPAT). Apart from that, there is also a code of ethics. With regard to the explanation above, the purpose of this study is 1) to find out the form of legal protection against the criminalization of notary/PPAT positions in the city of Semarang, 2) to find out and analyze how to recover the rights and conditions of a notary who is caught in criminalization in carrying out his position in the city of Semarang. The approach method in this research is a sociological juridical approach. The research specifications used are analytical descriptive research. Data types use primary data and secondary data. Data collection using interview and literature study methods. The data analysis method used is qualitative analysis. The results of the study concluded that: 1) by applying the precautionary principle before making a deed, in order to examine all facts related to making a deed with considerations based on statutory regulations. 2) Rehabilitation is a form of eliminating all losses that have been caused by cases that have befallen a notary and is a form of restoring the rights of a notary by clearing the good name, position, dignity and dignity as a public official. If it is related to the case example in Decision Number: 650/Pid.B/2015/PN Dps, the form of compensation can be submitted in pretrial because the indictment does not fulfill the elements of crime of violating a criminal act and the indictment used is a criminal act that is not in accordance with the elements contained in a criminal act but rather a civil act so that this has shown that there has been an error in the application of law.